Assignment of NMR data and Conformational analysis of larotrectinib and its precursors. (9th April 2021) - Lv, Xunlei; Zheng, Yan; Pan, Jing; Chen, Liang; Lin, Kuaile; Ye, Deyong; Zhou, Weicheng
Abstract: NMR experiments were used to identify the two main conformations of Larotrectinib and its synthetic precursor, the nitro compound 4 . Conformational analysis by dynamic NMR was performed in different temperature and solvents, combining 2D EXSY and NOE experiments. The results revealed the conformations of Larotrectinib and compound 4 were caused by the barrier to rotation of C11–N17. Meanwhile, the conformational specific structures of compound 4 were postulated based on NOE data and molecular simulation. The complete assignments of 1 H and 13 C NMR data for compounds 1, 4 and 5 were reported for the first time. Graphical abstract: Image 1 Highlights: Exchange dynamics process of larotrectinib and its precursors were identified as barrier to rotation of C11–N17 bond. The conformational structures of larotrectinib and its precursors were postulated based on NOE and molecular simulation. The complete assignments of 1 H and 13 C NMR data for larotrectinib and its precursors were reported for the first time.